2019
DOI: 10.1097/md.0000000000018016
|View full text |Cite
|
Sign up to set email alerts
|

Breast metastasis from colorectal cancer treated by multimodal therapy

Abstract: Introduction: Breast metastases from primary colorectal carcinoma are extremely rare, with only 45 cases being reported previously. Since the most common malignancy in the breast and axilla is primary breast cancer regardless of cancer history, non-hematologic metastases may be misdiagnosed initially. Nevertheless, differentiating breast metastases from primary breast cancer is crucial because of their differences in prognosis and management. Patient concerns: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…We have lack experience in the treatment of patients with rare site metastasis. For now, a majority of the patients with breast metastasis form colon received standardized management of their primary tumor [21]. If the patients recur with solitary nodules within the breast, surgical excision with negative margins may bene t for them [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…We have lack experience in the treatment of patients with rare site metastasis. For now, a majority of the patients with breast metastasis form colon received standardized management of their primary tumor [21]. If the patients recur with solitary nodules within the breast, surgical excision with negative margins may bene t for them [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…A majority of these patients received standardized management of their primary CRC[ 3 ], even if according to a recent report, the management of metastatic breast mass from CRC is often diagnostic and palliative[ 1 ]. Oral capecitabine, which was prescribed as palliative chemotherapy, might further slow the growth of the patient's metastasis in the breast[ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Breast metastases from other tumors are quite rare and account for only 0.5%-3% of all breast metastasis[ 1 , 2 ]. For colorectal cancer (CRC) metastatic to the breast, the differential diagnosis between rare non-mammary breast metastases and primary cancer is crucial because of the completely different approach in management and prognosis[ 3 ]. Patients with breast metastases from CRC generally have a poor prognosis, and the management is palliative.…”
Section: Introductionmentioning
confidence: 99%
“…The mean age at which breast metastases were detected was 52-year-old. Isolated breast metastases were found in 12 cases and in the majority of cases, breast metastases were diagnosed after a previous diagnosis of colorectal cancer [4,5]. Zhang et al reported one case in which the initial presentation was a breast lesion in an 80-year-old female patient with the primary sigmoid tumor that was identified later [6].…”
Section: Discussionmentioning
confidence: 99%
“…This is reasonable if the lump is mistaken for as primary breast cancer or becomes symptomatic as in our case. Unfortunately, the prognosis of patients with metastatic breast tumor of colorectal cancer origin is worse than the general colorectal cancer patients with distant metastases, with a 5-year survival rate of 13.8% due to the highly aggressive nature of breast metastasis from colorectal cancer [4].…”
Section: Discussionmentioning
confidence: 99%